Pesona Indonesia Pariwisata,Budaya,danSosial Lebih Dekat Mengenal Pulau Kalimantan - Yama Shita A. (PT Bintang Ilmu, 2009)
Pesona Indonesia Pariwisata,Budaya,danSosial Lebih Dekat Mengenal Pulau Kalimantan